Nutrition Education for Non-Health University Students in Indonesia: A Literature Review - Rusdatul Isma; Judhiastuty Februhartanty; Hendra Susanto (Journal of Global Nutrition, 2025)
Nutrition education is a method used to enhance knowledge and improve attitudes and practices regarding nutrition. Although studies prove its effectiveness among school students, there is a lack of evidence showing the effect of nutrition education implemented among university students, moreover those in non-health fields. This article examined various nutrition education programs designed for non-health university students in Indonesia to improve their nutritional knowledge, attitudes, and practices. The literature search was conducted using Google Scholar and Research Gate databases with the keywords in Bahasa Indonesia "edukasi gizi”, “intervensi gizi”, “pendidikan gizi”, and “mahasiswa non-kesehatan”, focusing on studies published between 2019 and 2024. Out of the 13 studies identified, 7 reported an increase in knowledge, 4 showed improvements in both knowledge and attitudes, 1 showed positive changes in knowledge, behaviour, and eating habits, and 1 indicated an increase in nutritional knowledge but the level of behavioral change was not consistently achieved.